2020
DOI: 10.3389/fgene.2020.603552
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on the Role of Histone Modification in Breast Cancer Progression and the Advanced Technological Tools to Study Epigenetic Determinants of Metastasis

Abstract: Metastasis is a complex process that involved in various genetic and epigenetic alterations during the progression of breast cancer. Recent evidences have indicated that the mutation in the genome sequence may not be the key factor for increasing metastatic potential. Epigenetic changes were revealed to be important for metastatic phenotypes transition with the development in understanding the epigenetic basis of breast cancer. Herein, we aim to present the potential epigenetic drivers that induce dysregulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 181 publications
(171 reference statements)
0
21
0
6
Order By: Relevance
“… 24 As a developmental program, EMT has a critical function in metastasis, and in the process of metastatic progression, some modifications both genetic and epigenetic can endow malignant cells with the properties that have effects on modulation of metastatic capacity. 25 , 26 E-Cadherin, N-Cadherin, and Vimentin are those EMT-related factors. 27 As two members of the Cadherin family, E-Cadherin and N-Cadherin are the most prominent cell adhesion molecules, and E-Cadherin is a glycoprotein with transmembrane ability, which is pivotal to cell-to-cell adhesion and acts as tumor-suppressor, while N-Cadherin, on the opposite confers malignant cells upon metastasis acquisition or promotion.…”
Section: Discussionmentioning
confidence: 99%
“… 24 As a developmental program, EMT has a critical function in metastasis, and in the process of metastatic progression, some modifications both genetic and epigenetic can endow malignant cells with the properties that have effects on modulation of metastatic capacity. 25 , 26 E-Cadherin, N-Cadherin, and Vimentin are those EMT-related factors. 27 As two members of the Cadherin family, E-Cadherin and N-Cadherin are the most prominent cell adhesion molecules, and E-Cadherin is a glycoprotein with transmembrane ability, which is pivotal to cell-to-cell adhesion and acts as tumor-suppressor, while N-Cadherin, on the opposite confers malignant cells upon metastasis acquisition or promotion.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have been suggested that epigenetic changes such as DNA methylation and histone modifications enhance the events of BCSC metastasis [126][127][128]. miRNAs are epigenetic modulators that target mRNAs without modifying the gene sequences [129,130].…”
Section: Signaling Pathways Induced By Mirnas In Bcscsmentioning
confidence: 99%
“…This complex impacts transcription through interactions with histone acetyltransferases (HAT), followed by chromatin changes (Campbell et al, 2010). An increasing body of evidence reveals that histones' modifications (including methylation and acetylation) are involved in breast cancer metastasis (extensively reviewed in Nandy et al, 2020;Zhuang et al, 2020). According to Saramäki and others (Saramäki et al, 2009) both the histone acetylation and methylation processes are involved in cyclic chromatin looping during regulation of p21 expression after 1,25(OH) 2 D 3 supplementation to breast cancer cells.…”
Section: Possible Epigenetic Impact On Changes In Vitamin D Metabolism Observed In Breast Cancer Patientsmentioning
confidence: 99%